2016
DOI: 10.1007/s00170-016-9509-0
|View full text |Cite
|
Sign up to set email alerts
|

A lightweight and support-free design method for selective laser melting

Abstract: Topology optimisation is an effective approach to design extreme lightweight components. However, most of the resulted optimum lightweight components usually have complex structures which cannot be produced successfully by traditional manufacturing processes. Selective laser melting is one of the additive manufacturing processes. It shows powerful capacity in the manufacturing of metal components with complex structures. Therefore, the combination of topology optimisation and selective laser melting shows a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…Lightweight design is one area that AM achieves well where it is impractical for other conventional fabrication technologies [1][2][3]. Currently there are two main methods of lightweight design, including cellular structure with unit cell [4][5][6] and topology optimization with advanced algorithm [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight design is one area that AM achieves well where it is impractical for other conventional fabrication technologies [1][2][3]. Currently there are two main methods of lightweight design, including cellular structure with unit cell [4][5][6] and topology optimization with advanced algorithm [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…More complex geometries, intricate networks of channels, additional layers and cantilever membranes, among other features and details, can be obtained following similar computer-aided design procedures, incorporating ad hoc support structures, leaving enough space for resin or slurry evacuation and applying lithography-based ceramic manufacture, either to ceramic and bioceramic slurries and to polymers and biopolymers, which constitutes and additional very unique feature of the technology used in this study. The presented process is aligned with current groundbreaking trends linked to light-weight design and to the minimization of support structures in additive manufacturing [28].…”
Section: Resultsmentioning
confidence: 97%
“…One of the most effective ways of lessening the use of the support and its associated cost is the optimum orientation of the part on the building platform [10,11,26]. The application of topology optimization can also be utilized to create a lightweight design that meets the support-free requirement [27,28]. Additionally, many research studies which have developed design rules for self-supporting overhangs can be found in the literature [10,15,17,[29][30][31][32].…”
Section: Literature Surveymentioning
confidence: 99%